PELAKSANAAN DISKRESI OLEH PENYIDIK DALAM TINDAK PIDANA KECELKAAN LALU LINTAS JALAN RAYA DI KOTA DENPASAR - Hendra Pratama, Si Putu; Sekar, I Dewa Nyoman (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 04, September 2013, 2013)
In a criminal case such as the case of traffic accidents in practice or reality can be settled out of court by using police discretion in consultation mechanism through kinship or term often familiar with ADR (alternative dispute resolution), which in fact it is cleary deviate from the provisions of article 360 paragraph (1) of the Criminal Justice Act, and therefore are expected for the future in terms of discretion by the investigator to be more clearly set boundaries to avoid abuse of authority.
Keywords: discretion,abuse of authority, the investigator, the traffic accidents